Analisis Pengaruh Kompetensi Profesional Dan Disiplin Kerja Terhadap Kinerja Guru Sekolah Swasta Di Jakarta - M. Yusuf Alfian Rendra Anggoro KR; Fauzie Senoaji; Tinto Wahyu Kisworo; Indri Lastriyani; Rosa Zulfikhar (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This study aims to analyze the effect of work discipline and professional competence on the performance of Muhamadiyah Matraman Middle and High School teachers in the Covid-19 pandemic situation. This study uses a quantitative approach. Methods of data collection using a questionnaire. The research method uses multiple analysis regression. The population in this research is teachers who work in SMP and SMA Muhammadiyah Matraman. The sampling technique used in this study was non-probability sampling and data analysis was processed using the SPSS 20 application. The results of the hypothesis test showed that the work discipline variable had no effect on teacher performance, the professional competence variable had an effect on teacher performance and the work discipline and professional competence variable had no effect on teacher performance. significant influence on teacher performance.